Immunogenicity and protective efficacy of SARS-CoV-2 recombinant S-protein vaccine S-268019-b in cynomolgus monkeys - Hashimoto, Masayuki; Nagata, Noriyo; Homma, Tomoyuki; Maeda, Hiroki; Dohi, Keiji; Seki, Naomi M.; Yoshihara, Ken; Iwata-Yoshikawa, Naoko; Shiwa-Sudo, Nozomi; Sakai, Yusuke; Shirakura, Masayuki; Kishida, Noriko; et al. (Vaccine, 2022)
•A novel SARS-CoV-2 recombinant spike (S)-protein vaccine S-268019-b was developed.•S-268019-b induced antibodies against S-protein and its receptor binding domain.•Neutralizing antibody was induced against SARS-CoV-2 and pseudovirus variants.•S-268019-b demonstrated protective efficacy against SARS-CoV-2 challenge.•S-268019-b was safe for use in cynomolgus macaques. The vaccine S-268019-b is a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S)-protein vaccine consisting of full-length recombinant SARS-CoV-2 S-protein (S-910823) as antigen, mixed with the squalene-based adjuvant A-910823. The current study evaluated the immunogenicity of S-268019-b using various doses of S-910823 and its vaccine efficacy against SARS-CoV-2 challenge in cynomolgus monkeys. The different doses of S-910823 combined with A-910823 were intramuscularly administered twice at a 3-week interval. Two weeks after the second dosing, dose-dependent humoral immune responses were observed with neutralizing antibody titers being comparable to that of human convalescent plasma. Pseudoviruses harboring S proteins from Beta and Gamma SARS-CoV-2 variants displayed approximately 3- to 4-fold reduced sensitivity to neutralizing antibodies induced after two vaccine doses compared with that against ancestral viruses, whereas neutralizing antibody titers were reduced >14-fold against the Omicron variant. Cellular immunity was also induced with a relative Th1 polarized response. No adverse clinical signs or weight loss associated with the vaccine were observed, suggesting safety of the vaccine in cynomolgus monkeys. Immunization with 10 µg of S-910823 with A-910823 demonstrated protective efficacy against SARS-CoV-2 challenge according to genomic and subgenomic viral RNA transcript levels in nasopharyngeal, throat, and rectal swab specimens. Pathological analysis revealed no detectable vaccine-dependent enhancement of disease in the lungs of challenged vaccinated monkeys. The current findings provide fundamental information regarding vaccine doses for human trials and support the development of S-268019-b as a safe and effective vaccine for controlling the current pandemic, as well as general protection against SARS-CoV-2 moving forward.